1999
DOI: 10.1093/protein/12.2.179
|View full text |Cite
|
Sign up to set email alerts
|

Efficient site specific removal of a C-terminal FLAG fusion from a Fab′ using copper(II) ion catalysed protein cleavage

Abstract: The peptide sequence (N)DKTH(C) was investigated as a site for efficient, specific cleavage of a fusion protein by cupric ions using a humanised gamma1 Fab' as a model protein. The native upper hinge (N)DKTH(C) sequence was mutated to create a site resistant to cleavage by cupric ions and a (N)DKTH(C) sequence introduced between the hinge and a C-terminal FLAG peptide. Incubation of Fab' with Cu2+ at 62 degrees C at alkaline pHs resulted in removal of the FLAG peptide with efficiencies of up to 86%. Cleavage c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 22 publications
0
14
1
Order By: Relevance
“…Although successful in this particular case, this approach was not converted into a generally applicable procedure [140,141].…”
Section: Practical Applications Of Metal-assisted Peptide Bond Hydrolmentioning
confidence: 99%
“…Although successful in this particular case, this approach was not converted into a generally applicable procedure [140,141].…”
Section: Practical Applications Of Metal-assisted Peptide Bond Hydrolmentioning
confidence: 99%
“…By using an anchoring amino acid side chain to substitute for the Nterminal group, Zn II should be capable of promoting hydrolysis of internal Ser(Thr)-Xaa sequences in intact proteins. In the case of Ni II [49], Pd II [89,91,92,96], Pt II [96], and even Cu II [32,33,75,90,94,95,98], hydrolytic cleavage of Ser(Thr)-Xaa protein sequences has been reported in the literature.…”
Section: Divalent Zincmentioning
confidence: 99%
“…Work with small peptides has led to the use of Cu II and Ni II ions to cleave intact proteins [32,33,49,90,95,130]. Horse heart myoglobin was hydrolyzed by CuCl 2 at Gln91- Fig.…”
Section: Copper(ii) and Nickel (Ii) Ionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Copper(II) ions have been shown to cleave several proteins, including the hinge region of human IgG antibodies [20]. Follow-up studies with Cu(II) ions showed specific hydrolysis of peptide bonds on the amino side of ser-his and thr-his sequences at high temperatures and basic conditions [21,22]. Myoglobin was also specifically cleaved by a series of Cu(II) reagents after Gln91 and Ala84 [23].…”
Section: Introductionmentioning
confidence: 99%